The Business Strategy Development of Bright IMC - Fuad, Rifqi; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2017)
Abstract. Marketing Communication Agency is a fast growing Industry for both in Indonesia and Worldwide. Bright IMC is one of the local agencies that try to compete in this industry. However, even though the industry itself is growing yet Bright IMC was having a performance downfall in 2016. This problem will be handled by analyzing the external and internal condition of the company and try to find the most suitable strategy to compete in 2017. PESTEL Analysis, Porter’s Five Forces, and Competitor Analysis are used as the External Analysis. Value Chain for Services (VCSE) and VRIO Model will be conducted as Internal Analysis. Root Cause Analysis was conducted in order to know the root problem that was happening in Bright IMC, and to explain more about the best strategy for Bright IMC is done by Strategy Diamond, Business Level Strategy and Business Model Canvas. In the last chapter, it is found that although there was some external problem that happened in 2016, yet the main problem of Bright IMC was actually on the unpreparedness of Bright IMC’s internal team to face their situations at that time. First, Bright IMC didn’t have a proper account team whereas the role of account in agency world is one of the most important roles where the communication between Bright IMC team with clients and determine whether the projects are acquired or determine client’s satisfaction in Bright service. Second, Bright IMC managerial team have never defined basic managerial needs such as Job Descriptions for all employees, agency’s workflow, the weak internal and external communication occurred, un-updated digital assets that are used for promotion, and in planning and mapping clients. Third, although Bright IMC stated that they have all services that are needed for client’s marketing communication needs, however, the quality of Bright IMC internal team is not yet capable enough to be classified as IMC agency. Based on findings, the author recommends implementation plans that hopefully will be able to help Bright IMC in facing their problems and to prepare them to be more ready to maximize their capability for years ahead.Keywords: Marketing Communication, Advertising Agency, IMC, Root Cause Analysis, Business Strategy, Business Level Strategy, Strategy Diamond, Business Model Canvas